2015
DOI: 10.1002/14651858.cd006537.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Laser treatment of drusen to prevent progression to advanced age-related macular degeneration

Abstract: Background Drusen are amorphous yellowish deposits beneath the sensory retina. People with drusen, particularly large drusen, are at higher risk of developing age-related macular degeneration (AMD). The most common complication in AMD is choroidal neovascularisation (CNV), the growth of new blood vessels in the centre of the macula. The risk of CNV is higher among people who are already affected by CNV in one eye. It has been observed clinically that laser photocoagulation of drusen leads to their disappearanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
0
5

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 79 publications
1
44
0
5
Order By: Relevance
“…It would have been ideal to have taken multifocal electroretinogram measurements after each laser application in order to assess preservation of retinal function at the site of treatment. Recent work using the 1.7 ms pulse duration SRT laser, which induces an RPE-specific response analogous to that of the 2RT laser [10,25], showed that subvisual SRT caused histological changes of the same magnitude as documented by subvisual 2RT in the current study, and negligible functional changes when assessed by multifocal electroretinogram [42]. Thus, it is reasonable to predict that since repeat 2RT laser did not induce histological damage additive to that of single application, then functional impairment would likewise not have increased.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It would have been ideal to have taken multifocal electroretinogram measurements after each laser application in order to assess preservation of retinal function at the site of treatment. Recent work using the 1.7 ms pulse duration SRT laser, which induces an RPE-specific response analogous to that of the 2RT laser [10,25], showed that subvisual SRT caused histological changes of the same magnitude as documented by subvisual 2RT in the current study, and negligible functional changes when assessed by multifocal electroretinogram [42]. Thus, it is reasonable to predict that since repeat 2RT laser did not induce histological damage additive to that of single application, then functional impairment would likewise not have increased.…”
Section: Discussionmentioning
confidence: 99%
“…Results to date have shown no clinically visible lesions or disease progression, reduced drusen load, and an improvement in flicker threshold [13,18]. It has been known for over 40 years that laser photocoagulation reduces drusen load in patients with AMD [19], but data pertaining to the risk of inducing exudative lesions have been contradictory [20][21][22][23][24][25]. The divergent results are believed to be related to the number and intensity of the laser burns, and the study inclusion criteria.…”
Section: Introductionmentioning
confidence: 99%
“…Thermal laser photocoagulation with continuouswave (CW) lasers was used in the 1990s and it was reported to reduce drusen load, a risk factor for progression to late-stage AMD. [10][11][12][13][14] However, these lasers result in thermal damage to the photoreceptors and inner retinal neurons, as the laser energy is converted to heat energy through absorption by the melanin in the RPE monolayer and choroid. 15,16 Some reports have also highlighted a potential increased risk of CNV, subretinal fibrosis, and microscotomas.…”
mentioning
confidence: 99%
“…[17][18][19][20] A Cochrane review of the literature for thermal laser treatments for AMD suggests that the frequency of CNV in AMD eyes is not different between laser-treated and the natural history cohorts when laser energy is within the clinical range. 10 However, when used at high-energy levels in mice, the thermal laser burn can break Bruch's membrane, leading to the growth of new choroidal vessels into the subretinal space, mimicking the neovascular form of human AMD. 21 Because of this, photocoagulation lasers are being used at high energy to induce a model of CNV in various animals, 21 and further use of thermal lasers for prophylactic treatment for early stages of AMD has not been continued.…”
mentioning
confidence: 99%
“…Retinal neovascularization exhibits two types of vessel growth: (i) vessel sprout in the anterior part of the retina and NFL, sometimes breaking through ILM and invading the vitreous, and (ii) vessel growth in the posterior direction, through outer retina towards sub-retinal space [3, 9, 10]. Laser based retinal photocoagulation is a clinically established non-invasive treatment procedure for diabetic retinopathy [11, 12]. …”
Section: Introductionmentioning
confidence: 99%